The Cohesiveness of Muslim Pangestu Members in Salatiga, Central Java - Suciati, S. (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2014)
The drying of spirituality and weakening of cohesiveness in the midst of materialistic hedonistic modern world become major challenge for the adherents of official religions in Indonesia. The practice of religions is considered too much focusing on ritual aspects. Therefore, those teachings cannot give the real meaningfulness of religious life. Consequently, some adherents of official religions begin to see other spiritual/mysticism sects. This study describes the social cohesiveness among muslims who become members of Pangestu, a spiritual-mysticism sect widely spreading among Javanese society in Indonesia. This research shows that the Pangestu in Salatiga, Central Java, can fulfill social, economic, and spiritual needs of its members. Among the underlying factors that make Pangestu succeed to meet its membersâ needs and expectations are the capability of the members to intensely communicate with each other through meetings and bawaraos (Jv, informal gathering), the great concern between members, good-example of leadership, the defense of Pangestuâs good name, and the satisfaction in experiencing meaningfulness of religious practices.[Kekeringan spiritual dan lemahnya kebersamaan di tengah dunia modern yang serba hedonistik menjadi tantangan utama bagi para pemeluk agama di Indonesia. Praktik-praktik keagamaan terlalu banyak terfokus pada aspek ritual, sehingga ajaran agama tidak mampu menghadirkan praktek-praktek keagamaan yang benar-benar bermakna. Hal ini mendorong sebagian pemeluk agama untuk melirik aliran kepercayaan dan kebatinan. Artikel ini mendeskripsikan keguyuban sosial di antara orang-orang Islam yang menjadi anggota Pangestu, sebuah aliran kepercayaan di Indonesia yang banyak menyebar terutama di kalangan masyarakat Jawa. Penelitian ini menunjukkan bahwa Pangestu di Salatiga, Jawa Tegah, mampu memenuhi kebutuhan sosial, ekonomi, dan spiritual para anggotanya. Di antara faktor yang menentukan keberhasilan Pangestu dalam memenuhi harapan para anggotanya adalah adanya komunikasi intensif antar anggota melalui pertemuan dan bawaraos (Jv, kumpul-kumpul), perhatian yang besar terhadap anggota lainnya, teladan kepemimpinan yang bagus, pembelaan terhadap nama baik paguyuban Pangestu, dan kepuasan dalam menyelami kebermaknaan praktik-praktik keagamaan.]